2018
DOI: 10.3171/2016.10.jns161355
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blinded, placebo-controlled trial comparing two multimodal opioid-minimizing pain management regimens following transsphenoidal surgery

Abstract: OBJECTIVE Pain control is an important clinical consideration and quality-of-care metric. No studies have examined postoperative pain control following transsphenoidal surgery for pituitary lesions. The study goals were to 1) report postoperative pain scores following transsphenoidal surgery, 2) determine if multimodal opioid-minimizing pain regimens yielded satisfactory postoperative pain control, and 3) determine if intravenous (IV) ibuprofen improved postoperative pain scores and reduced opioid use compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
1
48
1
2
Order By: Relevance
“…Of the 9 studies analyzed, 4 (Singla et al, 13 Shepherd et al, 25 Viswanath et al, 26 and Uribe et al 27 ) investigated the efficacy of IVIB using pain scores and postoperative opioid use. IVIB was reproducibly more effective in reducing postoperative pain and the quantity of opioids used than were placebo, IV acetaminophen, an analgesic regimen with placebo, oral acetaminophen, and IV ketorolac in patients undergoing orthopedic, trans-sphenoidal, third molar, and arthroscopic knee surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 9 studies analyzed, 4 (Singla et al, 13 Shepherd et al, 25 Viswanath et al, 26 and Uribe et al 27 ) investigated the efficacy of IVIB using pain scores and postoperative opioid use. IVIB was reproducibly more effective in reducing postoperative pain and the quantity of opioids used than were placebo, IV acetaminophen, an analgesic regimen with placebo, oral acetaminophen, and IV ketorolac in patients undergoing orthopedic, trans-sphenoidal, third molar, and arthroscopic knee surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Shepherd et al 25 measured postoperative pain; quantified the efficacy of multimodal, opioidminimizing pain management relative to the adequacy of postoperative pain control, and quantified postoperative pain and opioid use for comparisons between IVIB and IV placebo (saline). They randomized 62 adult patients undergoing transsphenoidal surgery for pituitary tumors to receive oral acetaminophen plus either IVIB or IV placebo, with rescue opioids given as needed in both groups.…”
Section: Studymentioning
confidence: 99%
“…7 Another small single-center, double-blinded study found that the addition of intravenous ibuprofen 800 mg to oral acetaminophen 1000 mg in patients undergoing transsphenoidal surgery reduced pain scores and opioid consumption over a 48-hour period. 8 Multimodal analgesia with intravenous acetaminophen and other nonsteroidal anti-inflammatory drugs (ketoprofen, diclofenac, and parecoxib) is supported by a number of studies. 17e19 The safety profile of the FDC was broadly comparable to either active agent alone.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence regarding the effect of combining ibuprofen and acetaminophen when one or both drugs are administered parenterally; published reports suggest that co-treatment affords superior pain relief. 7,8 To simplify multimodal analgesia and extend the therapeutic advantages of existing fixed-dose combination tablets to patients in whom parenteral administration is clinically justified, a fixed-dose combination containing ibuprofen 300 mg + acetaminophen 1000 mg in 100-mL solution for infusion has been developed (henceforth FDC). It has previously been shown that when given together by this route, there is no pharmacokinetic interaction between the 2 active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…through a single-level laminectomy. [17][18][19][20][21][22] Postoperatively, patients were either in the postanesthesia care unit until admitted to the PICU or directly admitted to the PICU. Starting on POD 1, patients were on the hospitalist service.…”
Section: Surgery and Postoperative Coursementioning
confidence: 99%